2014
DOI: 10.1073/pnas.1319955111
|View full text |Cite
|
Sign up to set email alerts
|

Salt stress-induced Ca 2+ waves are associated with rapid, long-distance root-to-shoot signaling in plants

Abstract: Their sessile lifestyle means that plants have to be exquisitely sensitive to their environment, integrating many signals to appropriate developmental and physiological responses. Stimuli ranging from wounding and pathogen attack to the distribution of water and nutrients in the soil are frequently presented in a localized manner but responses are often elicited throughout the plant. Such systemic signaling is thought to operate through the redistribution of a host of chemical regulators including peptides, RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
493
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 592 publications
(511 citation statements)
references
References 49 publications
(32 reference statements)
16
493
2
Order By: Relevance
“…We observed that stimulation of the seedlings by hyperosmotic stress resulted in a rapid, transient rise in [Ca 2+ ] i ( Fig. 1 A-D), consistent with previous reports (5,9,12,15). When seedlings were stimulated by a low-osmolarity solution iso-osmotic to the existing medium, only small responses were observed ( Fig.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…We observed that stimulation of the seedlings by hyperosmotic stress resulted in a rapid, transient rise in [Ca 2+ ] i ( Fig. 1 A-D), consistent with previous reports (5,9,12,15). When seedlings were stimulated by a low-osmolarity solution iso-osmotic to the existing medium, only small responses were observed ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…There is some debate about the site of initial generation of rapid hyperosmotic-induced Ca 2+ responses, and the site may depend on experimental conditions. Although some studies show that the Ca 2+ signal first appears in roots (9,12), another indicates that the Ca 2+ signal may occur simultaneously and more strongly in the shoots (15). The Ca 2+ response occurs in many cell types, but it is reported to be largest and to occur earliest within cells of the root epidermis (24,28).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations